Optimization of nucleic acid extraction and amplification of a thiamine biosynthesis gene fragment from selected Malaysian seaweeds - Md Ahaik, Fatin Amira; Mohd Taufik, Siti Hajar; Faiqah Johari, Nur Asna; Zainal Abidin, Aisamuddin Ardi; Balia Yusof, Zetty Norhana (Genetics Society of Japan, 2022)
Obtaining high-quality nucleic acid extracted from seaweeds is notoriously difficult due to contamination with polysaccharides and polyphenolic compounds after cell disruption. Specific methods need to be employed for RNA isolation in different seaweed species, and therefore studies of the thiamine biosynthesis pathway have been limited. Two selected Malaysian species which are highly abundant and underutilized, namely Gracilaria sp. and Padina sp., representing the red and brown seaweeds, respectively, were collected to develop optimized total RNA extraction methods. Prior to that, DNA was extracted, and amplification of the 18S rRNA gene and the THIC gene (encoding the first enzyme in the pyrimidine branch of the thiamine biosynthesis pathway) from the DNA template was successful in Gracilaria sp. only. RNA was then extracted from both seaweeds using three different existing methods, with some modifications, using cetyltrimethylammonium bromide, guanidine thiocyanate and sodium dodecyl sulphate. Methods I and III proved to be efficient for Padina sp. and Gracilaria sp., respectively, for the extraction of highly purified RNA, with A260 /A280 values of 2.0 and 1.8. However, amplification of the housekeeping gene glyceraldehyde-3-phosphate dehydrogenase and the THIC gene was successful in only Gracilaria sp. cDNA derived from extracted RNA. Further modifications are required to improve the exploitation of nucleic acids from brown seaweeds, which has been proven to be difficult. This work should pave the way for molecular studies of seaweeds generally and for the elucidation, specifically, of the thiamine biosynthesis pathway.